Leading through language : choosing words that influence and inspire - Egnal, Bart, 1979- (Hoboken : Wiley, 2015)
"Language in the business world is getting in the way of effective leadership. This book examines why language in the workplace is dull, confusing, or simply ineffective. It also considers why these failings undermine those who wish to demonstrate leadership when they speak. The solution is to use the language of leadership, a language that clearly and powerfully brings your ideas to life for your audience. This book teaches how to use words that engage and inspire everyone you speak with or write to. It will explain how to approach all communication as an act of leadership and then to use language that can convey ideas with energy, clarity, and conviction"--
Includes index.
Machine generated contents note: PREFACE AND ACKNOWLEDGMENTS ix INTRODUCTION xv Part I The Many Faces of Jargon Introduction to Part 1: Why Does Jargon Exist and Why Should Leaders Care? 1 Chapter 1 You Must Start with Leadership 11 Chapter 2 The (Few) Benefits of Jargon 19 Chapter 3 Assumption-Based Jargon 29 Chapter 4 Inflation Jargon 43 Chapter 5 Lack-of-Clarity Jargon 55 Chapter 6 Obfuscation Jargon 67 Part II Use the Language of Leadership Introduction to Part 2: Use the Language of Leadership 77 Chapter 7 Adopt the Leader's Mindset 83 Chapter 8 Script Yourself as a Leader 91 Chapter 9 Use the Language of Leadership 101 Chapter 10 The Language of Leadership Is. Visionary 109 Chapter 11 The Language of Leadership Is. Audience-Centric 117 Chapter 12 The Language of Leadership Is. Jargon-Free 129 Chapter 13 The Language of Leadership Is. Authentic 139 Chapter 14 The Language of Leadership Is. Passionate 147 Chapter 15 The Language of Leadership Is. Confident 157 Chapter 16 The Language of Leadership Is. Positive 167 Chapter 17 The Language of Leadership Is ... Direct 177 Chapter 18 The Language of Leadership Is. Concise 187 Chapter 19 The Language of Leadership Is. Professional 197 Chapter 20 The Language of Leadership Uses. Rhetoric 207 CONCLUSION 217 ABOUT THE AUTHOR 221 INDEX 000.
Print version record and CIP data provided by publisher.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Business communication; Business -- Language; Leadership; Communication dans l'entreprise.; Langue du commerce et des affaires; Leadership; BUSINESS & ECONOMICS -- Leadership; Business communication; Leadership